Electrochemically produced graphene with ultra large particles enhances mechanical properties of Portland cement mortar. (20th February 2020) - Ho, Van Dac; Ng, Ching-Tai; Coghlan, Campbell J.; Goodwin, Andy; Mc Guckin, Craig; Ozbakkaloglu, Togay; Losic, Dusan
Highlights: Pristine graphene (PRG) industrially produced by electrochemical process for cement mortar was explored. The ultra-large size of PRG particles in average of 56 ± 12 µm was confirmed. The 0.07% PRG is an optimal PRG dosage with 34.3% and 26.9% enhancement of compressive and tensile strengths at 28 days. PRG improves the microstructure of the cement matrix. A strong relationship between mechanical results and bonding gels, densities and arrangements of the crystals is revealed. PRG is promising a next-generation of additives in cementitious composites. Abstract: The effects of the dosages (0.01%, 0.03%, 0.05%, 0.07%, 0.1%, and 0.3% by weight of cement binder) of an ultra-large size (56 ± 12 µm) of pristine graphene (PRG) industrialy manufactured by electrochemical process on compressive and tensile strengths of cement mortars are presented. To have a better understanding of the reinforcement mechanism of PRG-cementitious gels, the physicochemical and microstructure analyses were performed. The results show that the addition of PRG to cement mortars improves their mechanical properties, with characteristic concentration dependence. The mortar mix with 0.07% PRG is identified as the optimal concentration, which provides 34.3% and 26.9% improvement in compressive and tensile strength at 28 days, respectively. This enhancement is attributed to the improvement of the hydration degree of cement paste, resulting in more Calcium Silicate Hydrate gel production. This also comes from the reinforcement of the adhesion bond that was created from friction forces between PRG sheets and cement gels, resulting in strengthening cement matrix composites and impeding crack propagations in the structure. However, with the further increases in PRG contents (i.e. 0.1%, 0.3%), the enhancement of mechanical properties of mortars is limited due to the impact of the van der Waals force on the sedimentation of PRG suspension, leading to the poor dispersion of the prepared PRG suspension. These results suggests that industrially produced pristine graphene by electrochemical process is a promising additive for improving performances of construction materials.